The European Union as Crisis Manager: Patterns and Prospects - Boin, Arjen; Ekengren, Magnus; Rhinard, Mark (Cambridge University Press, 2013)
The European Union is increasingly being asked to manage crises inside and outside the Union. From terrorist attacks to financial crises, and natural disasters to international conflicts, many crises today generate pressures to collaborate across geographical and functional boundaries. What capacities does the EU have to manage such crises? Why and how have these capacities evolved? How do they work and are they effective? This book offers an holistic perspective on EU crisis management. It defines the crisis concept broadly and examines EU capacities across policy sectors, institutions and agencies. The authors describe the full range of EU crisis management capacities that can be used for internal and external crises. Using an institutionalization perspective, they explain how these different capacities evolved and have become institutionalized. This highly accessible volume illuminates a rarely examined and increasingly important area of European cooperation.